2020
DOI: 10.1016/j.ebiom.2019.102600
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA X-inactive specific transcript silencing ameliorates primary graft dysfunction following lung transplantation through microRNA-21-dependent mechanism

Abstract: Background: Primary graft dysfunction (PGD) is a known acute lung injury (ALI) and a major cause of fatality post-lung transplantation. Though some long non-coding RNAs (lncRNAs) have been studied in ALI through regulation of microRNAs (miRNAs), their effects on PGD remain undefined. The present study aims to explore the underlying mechanism of lncRNA X-inactive specific transcript (XIST) in PGD after lung transplantation. Methods: Initially, the expression of miR-21, IL-12A and XIST was determined by RT-qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…LncRNA LUCAT1 could interact with PTBP1 and subsequently facilitate altered alternative splicing of DNA damage related genes in colorectal cancer [35]. LncRNA XIST have also been reported to down-regulate the expression of miR-21 as a miRNA sponge and subsequently increase the expression of IL-12A in primary graft dysfunction [36]. LncRNAs can be distributed in the cytoplasm, nucleus and other cellular substructures, and lncRNAs subcellular localization are closely related to their biology function and molecular roles [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LUCAT1 could interact with PTBP1 and subsequently facilitate altered alternative splicing of DNA damage related genes in colorectal cancer [35]. LncRNA XIST have also been reported to down-regulate the expression of miR-21 as a miRNA sponge and subsequently increase the expression of IL-12A in primary graft dysfunction [36]. LncRNAs can be distributed in the cytoplasm, nucleus and other cellular substructures, and lncRNAs subcellular localization are closely related to their biology function and molecular roles [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that XIST could interact with miRNAs [ 30 , 31 ]. For example, XIST was reported to deteriorate cervical cancer through regulating miR-124, miR-889-3p [ 42 ], suppress glioma progression by the upregulation of miR-204-5p [ 43 ], and accelerate the Primary graft dysfunction by binding to miR-21 [ 44 ]. However, the underlying molecular mechanism of XIST and miRNA in ALI has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Primary graft dysfunction (PGD), which is a major cause of fatality post-lung transplantation, is a known acute lung injury (ALI). Li et al (2020a) found that lncRNA Xist, which positively elevates the expression of IL-12A by acting as a ceRNA of miR-21, induces NET (neutrophil extracellular trap) formation and accelerates PGD after lung transplantation by activating the network of miR-21/IL-12A.…”
Section: The Role Of Lncrna Xist In Non-cancer Diseasesmentioning
confidence: 99%